Justification of the Possibility for Extending the Service Life of Cast Parts of a Three-Axle Bogie Based on Results of the Running Strength Tests to Determine Their Loading - Rustam Rahimov; Diyor Zafarov (Communications)
The article presents the results of research aimed at assessing the residual life and the possibility of extending the service life of cast parts of a UVZ-9M three-axle bogie used in six-axle scale test wagons. The tests have shown that the maximum stresses in the most stressed areas of the side frame, spring and pivot beams are within acceptable values, which indicates the presence of a residual life. The analysis of safety margin coefficients confirmed that the bogie elements have a significant reserve of operational characteristics. Calculations of the full service life of cast parts, performed based on the experimental data, demonstrated a sufficient residual life to prolong their use. It has been scientifically and experimentally proven that the cast parts of the UVZ-9M three-axle bogie can be safely operated for 5 years.